EVALUATION OF GROUNDWATER SUITABILITY FOR IRRIGATION PURPOSE USING GIS AND IRRIGATION WATER QUALITY INDICES - Adagba, Terlumun; Kankara, Aliyu Ibrahim; Idris, Musa Ado (FUDMA JOURNAL OF SCIENCES, 2022)
As a major source of water for irrigation, the evaluation and assessment of groundwater to ensure it meets the quality for sustainable agriculture is key. This research presents the findings of the quality of groundwater and its suitability for irrigation purposes. This was carried out using the irrigation water quality indices and the Geographic Information System (GIS). The Inverse Distance Weighted (IDW) method of the GIS was used to study the spatial distribution of these indices. Indices considered include Sodium Absorption Ratio (SAR), Percentage Sodium (%Na), Permeability Index (PI), Kelly Ratio (KR), Magnesium Hazard (MH), Total Hardness (TH), Residual Sodium Bicarbonate (RSBC) and Potential Salinity (PS). The values obtained were SAR (0.00 to 10.99, mean of 3.43), Percentage Sodium (26.00% to 94.42%, mean of 70.33%), Permeability Index (94.14% to 379.47%, mean of 161.45%), Kelly Ratio (0.00 to 8.62, mean of 3.19) and Magnesium Hazard (0.00% to 80.33 %, mean of 39.21%). Total Hardness (12.49 mg/L to 77.50 mg/L, mean of 31.35 mg/L), Residual Sodium Bicarbonate (-0.55 meq/L to 5.46 meq/L, mean of 1.41 meq/L), Potential Salinity (0.88 meq/L to 2.53 meq/L, mean of 1.69 meq/L) and Electrical Conductivity (110µS/cm to 910µS/cm, mean of 277.14µS/cm). The computed water indices when compared with known standards show that the groundwater from the study area is generally fit and can be applied for irrigation purposes.
Keywords: Geographic Information System, Groundwater Suitability, Irrigation, Irrigation Water Indices, Spatial Distribution